Perioperative chemotherapy in elderly patients with locally advanced adenocarcinoma of the stomach and the esophagogastric junction: a retrospective cohort analysis of toxicity and efficacy at the National Center for Tumor Diseases, Heidelberg - Haag, Georg Martin; Byl, Anne; Jäger, Dirk; Berger, Anne Katrin (Oncology, 2017)
Objective: Esophagogastric cancer occurs more frequently in older patients, but these are underrepresented in clinical studies establishing the current treatment standards for perioperative chemotherapy in locally advanced disease. This leads to uncertainty regarding the treatment of older patients with potentially toxic but active regimens. Methods: Using a prospectively generated database, we analyzed 63 patients aged ≥70 years undergoing perioperative chemotherapy for locally advanced esophagogastric cancer. The information included Eastern Cooperative Oncology Group (ECOG) performance status, comorbidity index, body mass index, regimen of chemotherapy, toxicity, dosage adjustments, date of surgery, application of adjuvant treatment, date of progression, and date of death. Survival times were calculated. Results: The median age was 73 years. 96.8% of the patients received an oxaliplatin-containing regimen. In 17.5% of the patients, the dosage was reduced, and treatment was previously permanently stopped in 7.9%; 80% of the patients underwent curatively intended surgery, but only 27.5% of those undergoing resection started adjuvant treatment. Major histological regression was observed in 21.6% of the patients. The median survival was 19.1 months. Significantly improved survival times were observed for patients undergoing surgery = 0.008) and for patients with a triplet therapy (= 0.004). Survival was worse for patients aged ≥75 years. Conclusion: perioperative treatment is feasible and effective in elderly patients with esophagogastric cancer.